2012
DOI: 10.1063/1.3681812
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties and spatial ordering in multilayered ZnMgTe/ZnSe type-II quantum dot structures

Abstract: We report the structural properties and spatial ordering of multilayer ZnMgTe quantum dots (QDs) embedded in ZnSe, where sub-monolayer quantities of Mg were introduced periodically during growth in order to reduce the valence band offset of ZnTe QDs. The periodicity, period dispersion, individual layer thickness, and the composition of the multilayer structures were determined by comparing the experimental high resolution x-ray diffraction (HRXRD) spectra to simulated ones for the allowed (004) and quasi-forbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…However, we found that the addition of Mg in the QD layers contributed to the higher x-ray scattering intensity of the SL peaks. 17 For ZnMgTe/ZnSe, we observed SL peaks up to fifth order compared to the ZnTe/ZnSe case, 4,25 where we could resolve SL peaks only up to second order.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…However, we found that the addition of Mg in the QD layers contributed to the higher x-ray scattering intensity of the SL peaks. 17 For ZnMgTe/ZnSe, we observed SL peaks up to fifth order compared to the ZnTe/ZnSe case, 4,25 where we could resolve SL peaks only up to second order.…”
Section: Resultsmentioning
confidence: 67%
“…The simulation result showed that the average thicknesses of the ZnMgTe layer containing QDs and ZnSe barrier are about 0.1 and 3.6 nm, respectively. 17 The simulation result also showed that while most of Te is confined inside the QD-containing layer, there is a small amount of Te ($1%) diffusion inside the barrier. It is also found that there is approximately 30% Mg within the ZnMgTe layer.…”
Section: E Estimation Of Bandgaps and Qd Energy Levelsmentioning
confidence: 82%
See 2 more Smart Citations
“…Liu et al [15] grown Mg x Zn 1-x Te (0 ≤ x ≤ 0.67) by molecular beam epitaxy on the (100) GaAs substrates and measured their band gap values by photoluminescence at 12 K, and by optical reflectivity at room temperature. Manna et al [16,17] reported the structural properties and spatial ordering of multilayer ZnMgTe quantum dots (QDs) embedded in ZnSe. Elakkad et al [18] investigated photoluminescence and optical properties of Mg x Zn l-x Te in the composition range 0 < x < 0.48.…”
Section: Introductionmentioning
confidence: 99%